THE USING METAPHOR OF KATO SERAH TERIMO TEXT IN BUNGO CULTURE - Magria, Vera (TELL - US JOURNAL, 2017)
This research examines about the kinds of metaphors that found in the kato serah terimo text in Bungo tradition and the meaning of it. This research applied descriptive qualitative research in which the data are obtained from kato serah terimo text. It took from Bungo official office.The data are collected by observational method supported by note-taking and interviewing technique. After analyzing the data, it is found that there are 10 metaphors included into three from four kinds of metaphor based on Leech (`1981) theory. There are animistic, synaesthetic and concrete to abstract of metaphor. Animistic metaphor dominant exists in kato serah terimo.